Aspects of antenatal antigen administration influence on glycosaminoglicans’ distribution in rat’s nasopharynx structures - Matvieishyna, T. M.; Hryhorieva, O. A.; Bohdanov, P. V.; Artiukh, O. V.; Матвєйшина, Тетяна Миколаївна; Григор'єва, Олена Анатоліївна; Богданов, Павло Валерійович; Артюх, Олена Вікторівна (My University, 2021)
The purpose of the work was to establish features of glycosaminoglycans’ (GAG) distribution in a nasal part of rat’s pharynx in the postnatal period after antenatal antigen administration on a fetus.